Performance analysis of automatic grass chopper and grass vacuuming machine with gasoline engine drive system - Niko Andreas Hutabarat; Winfronstein Naibaho; Saloom Hilton Siahaan (EDUCTUM: Journal Research, 2026)
This study aims to design and analyze the performance of an automatic grass chopper and vacuum cleaner with a gasoline engine drive system as an appropriate technological solution to improve environmental cleaning efficiency. The main problem in this study is that the grass cleaning process is still done manually, which requires time, energy, and significant operational costs. The research method used is the design method which includes the design, assembly, and performance testing stages of the tool. The machine was designed using a Honda GX 200 gasoline engine, a centrifugal blower, a pulley transmission system, a grass chopper, and a container for the chopped results. Tests were conducted based on variations in engine speed to determine the chopping capacity, noise level, and fuel consumption. The results showed that the machine is able to carry out the cutting, chopping, and vacuuming processes of grass in an integrated manner with more effective performance than the manual method. Under optimal conditions, the machine is able to produce grass chopped up to 2.5 ounces in 6 minutes with an average noise level of 96.4 dB. In addition, the use of the machine has been proven to speed up the work process and reduce the need for manual labor. Thus, the designed machine has the potential to become an efficient and applicable technological innovation in supporting environmental cleanliness.